Fire and fury - Blade, Adam (Blade, Adam. Chronicles of Avantia, 2013)
Tanner, his companions, and the Beasts head for a final showdown with Derthsin when they discover that the last piece of the Mask of Anoret can be found in Derthsin's lair.